Análise econômica do peso de abate de bovinos confinados usando diferentes indicadores financeiros - Fabricio, Edom de Avila (2016)
Given the necessity to adopt techniques with the aim of predict the viability of the investment and know the real economic result, alternatives using simulation and joint analysis of various indicators, can provide consistent information to assist decision making. The objective of this study was to evaluate various financial indicators, estimated deterministically, on the economic feasibility of finishing steers commercialized with different weights, using the simulation technique. A deterministic analysis was conducted, simulating performance data steers with average initial weight of 350 kg, fed in confinement for slaughter with 410, 440, 470, 500, 530, 560 and 590 kg. The feeding period varies from 46 to 185 days, respectively. The date of the sale was the same for all weights on the highest price of the year, varying the date of purchase. Based in various economic indicators, the viability of the investment decreased linearly according to the increase in weight. The net present value was R$ 41,18, R$ 41,04, R$ 10,06, R$ -27,31, R$ -9,88, R$ -28,37, R$ -37,37, the index benefit: cost R$ 1,029, R$ 1,028, R$ 1,004, R$ 0,997, R$ 0,996, R$ 0,989, R$ 0,986, Additional Return on Investment 0,96, 0,92, 0,11, -0,06, -0,07, -0,18, -0,20% per month and Internal Rate of Return 1,69, 1,64, 1,00, 0,61, 0,79, 0,66, 0,65% per month, respectively from lowest to highest weight. The use of confinement as termination option to obtain the direct benefits of this technology is an alternative investment with low economic return.